Analisis Implementasi Green Supply Chain Management Pada Recycle Kemasan Plastik Produk Kecantikan - Putri, Atikah Nur Aini (Jurnal Kewirausahaan dan Inovasi, 2024)
The large-scale plastic production and consumption have become crucial environmental issues as they do not only affect the environment’s quality but also pose a serious challenge in the management of plastic waste. The negative impact of discontinuity in the plastic production and consumption cycles can be overcome using circular economy through waste management and supply chain management strategies. This study examines Green Supply Chain Management (GSCM) as an approach to handle the problem by focusing on the collaboration for managing the plastic package waste of Sociolla beauty products, which is recycled by Paste Laboratory into valuable products. The objective of this research is to analyze the implementation of GSCM at Paste Laboratory using Green SCOR and Analytical Hierarchy Process (AHP). This study finds that the GSCM performance score is 71, which belongs to the Good category, with consistent results in Make and Plan criteria as the most important activities in the decision making. However, there are indicators of Make that have the scores of below average according to the company’s achievement target; they are make cycle time, adherence to production schedule, number of trouble machines, and percentage of employee trained on environmental requirements.   Abstrak Produksi dan konsumsi plastik berskala besar menjadi isu lingkungan yang mendesak. Hal ini tidak hanya mempengaruhi kualitas lingkungan, tetapi juga menimbulkan tantangan serius pada pengelolaan sampah plastik. Dampak negatif dari ketidakberlanjutan pada siklus produksi dan konsumsi plastik dapat diatasi dengan circular economy melalui strategi waste management dan manajemen rantai pasok. Penelitian ini menyoroti Green Supply Chain Management (GSCM) sebagai pendekatan untuk mengatasi masalah tersebut, dengan fokus pada kolaborasi terhadap pengelolaan sampah kemasan plastik produk kecantikan dari Sociolla yang didaur ulang oleh Paste Laboratory menjadi produk bernilai. Tujuan penelitian ini adalah menganalisis implementasi GSCM di Paste Laboratory menggunakan model Green SCOR dan metode Analytical Hierarchy Process (AHP). Hasil penelitian ini menunjukkan nilai kinerja GSCM yaitu 71 yang tergolong kategori “Good” dengan hasil yang konsisten pada kriteria Make dan Plan sebagai prioritas aktivitas terpenting dalam pengambilan keputusan. Namun, beberapa indikator Make memiliki nilai di bawah rata-rata dari target capaian perusahaan, seperti make cycle time, adherence to production schedule, number of trouble machines, dan % of employee trained on environmental requirements.